Jaw Mobility Restoration through Physiotherapy After Prolonged Dental Procedures: A Pilot Study - Neha Singh Roda (Oral Sphere Journal of Dental and Health Sciences, 2025)
Long-term dental procedures may call for extended mouth opening, which might lead to temporomandibular joint pain, trismus, reduced jaw mobility following surgery, and so on. These problems impair important skills, including chewing, speaking, and maintaining tooth cleanliness, in addition to making one uncomfortable. Physiotherapy is a non-invasive and quick fix aimed to restoring normal jaw function by lowering muscular tension, improving joint flexibility, and thereby boosting the general range of motion. This research explores the efficiency of physiotherapeutic treatments, including thermosapy, manual therapy, passive stretching, and guided jaw exercises, in aiding functional recovery of the temporomandibular joint following significant dental treatments. Patients undertaking physiotherapy reported much improved masticatory ability, less pain, and jaw mobility. The findings underline the probable benefits of adding PT into postoperative therapy strategies to help with faster recovery and improved patient quality of life. Patient education, home-based exercise adherence, and a coordinated multidisciplinary approach combining dental specialists, physiotherapists, and pain experts are guarantees of best therapeutic effects. The study confirms the fundamental component of total dental treatment— physiotherapy inclusion especially in cases when extended treatments raise a patient's functional restrictions of the jaw.